Why Garden? Personal and Abiding Motivations for Community Gardening in New York City. Issue 10 (3rd October 2018) - Sonti, Nancy Falxa; Svendsen, Erika S.
Abstract: We explore the underlying motivations of NYC community gardeners in order to gain greater insight into how these valued public resources support individual and community well-being. Semi-structured interviews were used to capture a range of enduring gardener motivations over time. We find that the underlying motivations of NYC community gardeners are both personal and collective. For many, community gardens provide a space for reflection and for profound connection to the natural world. Gardening was reported to be restorative, and to help to strengthen an individual's connection to a larger community or cultural heritage. Themes of joy and personal fulfillment were consistently most prevalent over time, while the impulse to improve the community decreased in prevalence, and food production and cultural identity connections became more common motivations, possibly reflecting broader social shifts in NYC neighborhoods.